Two new species of Paratanakia (Teleostei: Cyprinidae) from Taiwan and mainland China - Chen, I-Shiung; Shy, Jhy-Yun (Zootaxa, 2024)
Two new species of bitterling of Paratanakia were found and collected from Taiwan island and Fujian Province, mainland China recently. Paratanakia fuvlidorsalis n. sp. which is endemic in Taiwan island can be well distinguished from other congeners by the following unique combination of features: (1) fin ray counts: dorsal fin rays 3, 8; anal fin rays 3, 10; pectoral fin rays modally 1, 12; (2) squamtion: lateral-line scales modally 34; and (3) its own specific dorsal fin color pattern in male. Paratanakia julongjiangensis n. sp. which is endemic in Fujian Province, mainland China can be well distinguished from other congeners by the following unique combination of features: (1) fin ray counts: dorsal fin rays 3, 9; anal fin rays 3, 11; pectoral fin rays modally 1, 12; (2) lateral-line scales modally 34; and (3) its own specific dorsal fin color pattern in male. The brief morphological comparison with close related species would be also addressed.